(untitled) (Eurasian Journal of Ecology, 2018)
The article presents geobotanical characteristics and floristic analysis of the communities with narrowly endemic species Oxytropis almaatensis, which found by us in the part of the spruce belt of the Trans-Ili Alatau mountains in Big Almaty gorge. By the authors noted that Oxytropis almaatensis is really narrowly endemic plant that grows on loose scree slope of the mountains and on the alluvial soils of mountain rivers. The plant occupies a limited area and its area is ruptured, even within the same gorge. However, living state of Oxytropis almaatensis in Trans-Ili Alatau mountaibs is good. Here can be found all life forms of the species, ranging from seedlings and juveniles, ending by senile individuals. Moreover the plants are blooming profusely and bear fruit annually. There is no direct threats to the population of Oxytropis almaatensis, because of the whole area of plant population is protected territory of Ili-Alatau National Park. However, loose scree on the slope of the mountains and alluvial sandy-gravelly soil of the valley of mountain river can be easily changed depending on the snow cover thickness, the spring floods and summer floods characters. Taking this into consideration, the authors recommend to constantly monitoring those areas where the Oxytropis almaatensis populations were found, thus, to keep under control the population state. Key words: Dominant, subdominant, phytocoenosis, life form, hemicryptophyte, terofit, mesophyte, xerophyte.